Current status and influencing factors of spiritual needs of patients with advanced cancer: a cross-sectional study - Xin Shi; Fengxia Wang; Lixin Xue; Zhaohong Gan; Yan Wang; Qian Wang; Xiaorong Luan (BMC, 2023)
Abstract Background Spiritual needs have been associated with better physical health outcomes and provide a context for patients to gain hope and significance in coping with disease. This study aimed to understand the status of spiritual needs of patients with advanced cancer and conducted a quantitative study on the relationship between patient-reported physical, psychological, and social influencing factors and spiritual needs based on a biopsychosocial-spiritual model. Methods In this study, 200 oncology inpatients from Shandong Province were recruited using a convenience sampling method to conduct a cross-sectional survey using general data from December 2020 to June 2022. Correlation analysis was used to analyze the correlation between spiritual needs and cancer-related fatigue, anxiety and depression, the family care index, and social support. Multiple regression analysis was used to analyze the relationship between spiritual needs and the influencing factors. Results The spiritual needs score of the patients with advanced cancer was high. Multiple regression analysis revealed that cancer-related fatigue, social support, and religious beliefs influenced the spiritual needs of patients with advanced cancer. Compared with married patients, widowed or divorced patients scored 8.531 points higher on spiritual needs. Cancer-related fatigue, social support, religious beliefs, and marital status (divorced or widowed) explained 21.4% of the total variation in the spiritual needs of patients with advanced cancer. Conclusion The spiritual needs of patients with advanced cancer were significantly correlated with cancer-related fatigue, depression, social support, and other factors. Religious beliefs, marital status, cancer-related fatigue, and social support were the main factors influencing the spiritual needs of patients with advanced cancer. This is a quantitative study, and medical staff can provide targeted spiritual care for patients with cancer based on the above influencing factors.